2005
DOI: 10.1016/j.jcomdis.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative and qualitative assessment of verbal short-term memory and phonological processing in 8-year-olds with a history of repetitive otitis media

Abstract: As a result of this activity, the participant will be able to (1) explain the outcome of recurrent OME before age 3 on later language and verbal STM development, (2) be aware of the complex relationships that link language development and verbal STM, (3) explain how fluctuant hearing loss during infancy and early childhood could affect verbal STM development and learning capacity for new phonological information, (4) describe different verbal STM measures that distinguish retention capacities for phonological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Among those mechanisms, increased proliferation of lymphadenoid tissues in the upper airways appears to be the most logical process, considering the prominent role of enlarged adenoids in increased upper airway resistance as well as in the pathophysiology of eustachian tube dysfunction. Based on our findings, it could be important to screen for HS among all children with ROM, particularly when considering the neurobehavioral implications of HS and ROM (2,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 84%
“…Among those mechanisms, increased proliferation of lymphadenoid tissues in the upper airways appears to be the most logical process, considering the prominent role of enlarged adenoids in increased upper airway resistance as well as in the pathophysiology of eustachian tube dysfunction. Based on our findings, it could be important to screen for HS among all children with ROM, particularly when considering the neurobehavioral implications of HS and ROM (2,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 84%
“…With regard to hearing, although there is some suggestion that there may be an impact on some subtle language skills (e.g., aspects of phonological processing or verbal working memory; Majerus et al, 2005 ; Nittrouer & Burton, 2005 ), a strong body of evidence suggests that the impact of otitis media and associated hearing loss on the development of speech and language is negligible ( Paradise et al, 2005 , 2007 ; Roberts, Hunter, et al, 2004 ; Roberts, Rosenfeld, & Zeisel, 2004 ). The contrast in these findings may relate to the differences in when the measures were taken.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conjectured that these lags resulted from underspecified phonological representations in WM due to hearing disruption early in life. Similarly, Majerus et al (2005) found that 8-year-old children with normal hearing and vocabulary at the time of test who had experienced severe and recurrent otitis media prior to the age of 3 performed lower than control children on tasks of PWM, including speeded nonword repetition and rhyme judgement. Finally, 5-year-olds who had experienced repeated episodes of otitis media prior to the age of 3 but with normal hearing at the time of testing showed reduced performance on tasks of syllable and phoneme awareness as well as on serial recall of word lists and comprehension of syntactically complex sentences (Nittrouer & Burton, 2005).…”
Section: A Spectrum Of Early Experiences In Language Acquisitionmentioning
confidence: 92%